PENATALAKSANAAN FISIOTERAPI PADA KONDISI TRIGGER FINGER DENGAN INTERVENSI ULTRASOUND (US), INFRARED (IR) DAN TRANSVERSE FRICTION DI RSUD BENDAN PEKALONGAN - Ari Santoso; Eko Budi Prasetyo (Universitas Widya Husada Semarang, 2018)
Trigger finger or tenosyvitis stenosing is described as a condition wherethe finger tendon is locked at the time of movement from the flexion positiontoward the extension position. This is due to local inflammation or the presence ofswelling in the flexor tendon wrap that causes the wrapper can not normally flow.Signs and symptoms that arise is the presence of pain, the spasm M. FleksorDigitorum, decreased strength of M. Fleksor Digitorum, limitations of fingerjoints. Physiotherapy modalities used include: ultrasound, infra red and transversefriction.To know the benefits of therapy with ultrasound modality, infra red andtransverse friction in relieving pain, reducing spasm M. Flexor Digitorum,increasing muscle strength M. Flexor Digitorum, increasing the scope of fingerjoint motion. Management of physiotherapy on finger trigger conditions withultrasound, infrared, and transverse friction modalities. After receiving physiotherapy treatment (ultrasound, infra red and transferfriction) for 6 times the therapy was obtained: 1) Decreased the tenderness of theflexor tendon from T1: 5.1 cm to T6: 0.9 cm, 2) Increased scope of joint motion inthe left PIP II of T1: S = 20º-0º-30º to T6: S = 28º-0º-60º and MCP II T1: S = 10º0º-30ºto T6:S=14º-0º-59º,3)Increased strength of M.Flexor Digitorum on PIP II Sinistra from T1: 4 to T6: 5, 4) Decreased the spasm of M. Fleksor Digitorum from T1: 1 to T6: 0. Ultasound, infra red and transverse friction can reduce pain,reduce spasm M. Flexor Digitorum, increase strength M. Flexor Digitorum,increase the scope of joint motion.